Implementasi Program Kampus Mengajar Angkatan 6 terhadap Budaya Literasi Siswa di SDK Nuabosi - Tai, Maria Yulianti; Ngura, Elisabeth Tantiana; Fono, Yasinta Maria; Ita, Efrida (LP. Ma'arif Janggan Magetan, 2024)
The Merdeka Learning Independent Campus (MBKM) program launched by the government of the Ministry of Education Culture Research and Technology (Kemendikbutristek). The teaching campus is part of the independent campus program which provides a forum for students to learn and develop themselves at the assignment school. This research focuses on the implementation of the Teaching Campus Program on student literacy culture at SDK Nuabosi. This study aims to understand how the Teaching Campus Program has been implemented at SDK Nuabosi and its impact on the development of a literacy culture. The research method used is a qualitative approach. The data collection techniques in this research are observation and documentation. This technique is used on data that is not measurable in the form of numbers or statistics. Qualitative data can be in the form of text, interviews, observations, and others. In qualitative data analysis techniques, researchers or analysts analyze the issues that arise in the data, understand the thoughts of participants, and interpret the meaning of the data. Some commonly used qualitative data analysis techniques are content analysis, discourse analysis, and grounded theory. Based on the results of the research conducted, through fun activities as an effort to implement a culture of literacy, students at SDK Nuabosi become more enthusiastic and have the motivation to further increase students' interest in reading.